(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Healthy and balanced nutrition is vital for individuals with Down syndrome. Proper nutrition ensures the proper intake of essential nutrients and prevents long-term health complications. This information sheet encompasses dietary recommendations for children and adults with Down syndrome.